2019
DOI: 10.4236/ijaa.2019.93014
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Interplanetary Shocks Associated with Six Major Geo-Effective Coronal Mass Ejections during Solar Cycle 24

Abstract: A Coronal Mass Ejection (CME) is an ejection of energetic plasma with magnetic field from the Sun. In traversing the Sun-Earth distance, the kinematics of the CME is immensely important for the prediction of space weather. The objective of the present work is to study the propagation properties of six major geo-effective CMEs and their associated interplanetary shocks which were observed during solar cycle 24. These reported CME events produced intense geo-magnetic storms (Dst > 140 nT). The six CME events hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Syed Ibrahim et al (2019 found that the ICME transit-time decreases with the increase in the CME initial speed, although a broad range of transit times were observed for a given CME speed. For slow CMEs ( < 400 km/s), the energy is transferred from the solar wind to the CMEs, while faster events (P400 km/s) tend to lose their energy to the ambient medium (e.g., Soni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Syed Ibrahim et al (2019 found that the ICME transit-time decreases with the increase in the CME initial speed, although a broad range of transit times were observed for a given CME speed. For slow CMEs ( < 400 km/s), the energy is transferred from the solar wind to the CMEs, while faster events (P400 km/s) tend to lose their energy to the ambient medium (e.g., Soni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However Weak and moderate storms could be caused by both CMEs and co-rotating interaction regions (CIRs) (Gosling et al, 1990). Primary requirements for the geo-effectiveness of CMEs are (1) the CME must be reach at Earth and (2) having southward component of their magnetic field (Soni et al, 2019). To determine the geo-magnetic effects of CMEs, we consider the minimum Dst values 1-5 days after the CME onsets.…”
Section: Geo-effectiveness Of Cmes/flaresmentioning
confidence: 99%